2022
DOI: 10.1097/pcc.0000000000002955
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children and Acute Kidney Injury: Retrospective Study of Five Italian PICUs

Abstract: Multisystem inflammatory syndrome in children (MIS-C) manifests with heart dysfunction and respiratory failure some weeks after a severe acute respiratory syndrome coronavirus disease 2 infection. The aim of our study was to explore the prevalence, severity, timing, and duration of acute kidney injury (AKI) in MIS-C patients. Furthermore, we evaluated which clinical variables and outcomes are associated with AKI.DESIGN: Multicenter retrospective study. SETTING:Five tertiary hospital PICUs in Italy. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…In our study, AKI presented a self-limiting course with no patients needing renal replacement therapy and only one presenting with hypertension at 6-month followup. Our results are different from other reports, in which renal replacement therapy has been reported in up to 15% of patients with MIS-C and kidney involvement [20][21][22]26,27]. Since in our cohort AKI subgroup presented with a more severe disease course, requiring more frequently intensive care support and second line immunomodulatory therapy, we may suppose that a prompt diagnosis and support with a more aggressive therapeutical approach may have favored a complete recovery in our patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, AKI presented a self-limiting course with no patients needing renal replacement therapy and only one presenting with hypertension at 6-month followup. Our results are different from other reports, in which renal replacement therapy has been reported in up to 15% of patients with MIS-C and kidney involvement [20][21][22]26,27]. Since in our cohort AKI subgroup presented with a more severe disease course, requiring more frequently intensive care support and second line immunomodulatory therapy, we may suppose that a prompt diagnosis and support with a more aggressive therapeutical approach may have favored a complete recovery in our patients.…”
Section: Discussioncontrasting
confidence: 99%
“…According to a recent systematic review and meta-analysis, up to one fifth of children with MIS-C develops AKI with the need of kidney replacement therapy in 5-37% of cases [20]. Moreover, AKI seems to be a negative prognostic factor since it is associated with higher probability of death and pediatric intensive care unit (PICU) admission [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This appears consistent with reports that MIS-C develops a mean 2–6 weeks after infection with COVID-19. In addition, children with AKI have significantly lower serum albumin levels and higher white blood cell counts than those without AKI at admission [ 6 , 14 , 18 ].…”
Section: Kidney Complications Associated With Covid-19 Infection In C...mentioning
confidence: 99%
“…11) Moreover, several observational studies of various sizes conducted from the beginning of the pandemic reported AKI incidence rates as high as approximately 11%-46% in children and adolescents with COVID-19 who are critically ill or developed MIS-C, similar to those observed in adults. 8,[12][13][14][15][16][17][18][19][20] In contrast, only a few studies reported the incidence of AKI in those with mild to moderate COVID-19. A multicenter cross-sectional study conducted in Turkey reported incidence rates of 16.9% for AKI and 31% for subclinical AKI.…”
Section: Kidney Complications Associated With Covid-19 Infection In C...mentioning
confidence: 99%
“…T here has been increasing interest in the development of quantitative methods for evaluating the clinical status of critically ill children, partly due to advances in technology, improved data collection and analysis, and access to a wealth of electronic health record (EHR) data (1)(2)(3)(4)(5). The pediatric Sequential Organ Failure Assessment (pSOFA) score is one of these methods developed for the quantitative evaluation of the severity of illness of PICU patients (6)(7)(8). The score is an adaptation of the adult SOFA score that assesses the severity of organ dysfunction across six organ systems (9).…”
mentioning
confidence: 99%